GORD and Barrett's oesophagus after bariatric procedures: multicentre prospective study. Issue 12 (5th November 2021) - Genco, Alfredo; Castagneto-Gissey, Lidia; Gualtieri, Loredana; Lucchese, Marcello; Leuratti, Luca; Soricelli, Emanuele; Casella, Giovanni
Abstract: Introduction: Gastro-oesophageal reflux disease (GORD) after bariatric surgery is a debated topic. This study investigated the prevalence of GORD and associated oesophageal complications following bariatric procedures—namely, adjustable gastric banding (AGB), sleeve gastrectomy (SG), Roux-en-Y gastric bypass (RYGB), and one-anastomosis gastric bypass (OAGB). Methods: This was a prospective multicentre study designed to evaluate the long-term effects of bariatric surgery on GORD. Patients were studied at baseline, at >10 years following AGB, SG, and RYGB, and at >3 years following OAGB (due to the more recent recognition of OAGB as a standard bariatric procedure). Patients were assessed by endoscopy and GORD symptom evaluation. Results: A total of 241 patients were enrolled. A minimum follow-up of 10 years was completed by 193 patients following AGB (57 patients), SG (95 patients), and RYGB (41 patients), and of >3 years by 48 subjects following OAGB. GORD symptoms increased following AGB and SG (from 14 to 31.6 per cent and from 26.3 to 58.9 per cent, respectively; P  < 0.0001), improved following RYGB (from 36.6 to 14.6 per cent; P  < 0.0001), and were unchanged following OAGB. The overall prevalence of erosive oesophagitis was greater in the SG group (74.7 per cent) than in the AGB (42.1 per cent), RYGB (22 per cent), and OAGB (22.9 per cent) groups ( P  < 0.0001). Barrett's oesophagus was found only in patients who had SG (16.8 per cent). Biliary-like gastric stagnation was found in a greater proportion of SG and OAGB patients (79.7 and 69.4 per cent, respectively) than in other treatment groups ( P  < 0.0001). The prevalence of biliary-type reflux into the oesophagus was higher in patients who underwent SG (74.7 per cent), compared with other treatment groups. Conclusion: Bariatric surgery leads to gastro-oesophageal complications of variable severity, particularly SG, which can result in a large proportion of patients developing Barrett's oesophagus. Lay Summary: Gastro-oesophageal reflux disease (GORD)-related oesophageal sequelae following bariatric surgery confirm the importance of postoperative endoscopic surveillance in early detection of such conditions. Sleeve gastrectomy was shown to be correlated with the highest prevalence of GORD, biliary-type gastric and oesophageal reflux, and erosive oesophagitis. This, in turn, appeared to be responsible for the high number of cases of Barrett's oesophagus found in this group of patients. Adjustable gastric banding displayed minimal effectiveness in terms of weight loss, along with a high number of reoperations, also due to band-related complications. The study showed one-anastomosis gastric bypass to be associated with a high percentage of subjects who developed often severe inflammation of the gastrojejunal anastomosis or of the gastric pouch, as a consequence of chronic biliary-type duodenogastric reflux. Finally, our results suggest that Roux-en-Y gastric bypass could represent the most 'reliable' bariatric procedure in terms of GORD resolution, and the only operation not requiring any reintervention in our cohort of patients. Each surgical procedure leads to gastro-oesophageal modifications of variable extent, which need to be taken into consideration when selecting the designated bariatric operation. Abstract : Gastro-oesophageal reflux disease (GORD)-related oesophageal sequelae following bariatric surgery confirm the importance of postoperative endoscopic surveillance for early detection of such conditions. Sleeve gastrectomy was shown to be correlated with the highest prevalence of GORD, biliary-type gastric and oesophageal reflux, and erosive oesophagitis. This, in turn, appeared to be responsible for the high number of cases of Barrett's oesophagus found in this group of patients. Adjustable gastric banding displayed minimal effectiveness in terms of weight loss, along with a high number of reoperations, also due to band-related complications. The study showed one-anastomosis gastric bypass to be associated with a high percentage of subjects who developed often severe inflammation of the gastrojejunal anastomosis or of the gastric pouch, as a consequence of a chronic biliary-type duodenogastric reflux. Finally, our results suggest that Roux-en-Y gastric bypass could represent the most 'reliable' bariatric procedure in terms of GORD resolution, and the only operation not requiring any reintervention in our cohort of patients. Each surgical procedure leads to gastro-oesophageal modifications of variable extent, which need to be taken into consideration when selecting the designated bariatric operation.